Analisis Pengaruh Perubahan Kecepatan Udara Pada Saluran Penampang Persegi - Chandra Buana (Jurnal Teknik Mesin Sinergi, 2009)
The study is aimed at finding out the influence of hydraulic radius to equivalent length of fully developed flow; and identifying the characteristics of boundary layer ‘development’ when it reaches the fully developed area as a result of hydraulic radius-changes. The hydraulic radius of each was made different, but their height was the same; i.e. 200 mm. The first wind tunnel’s width was 270 mm, the second was 320 mm, and the other one was 400 mm. The results reveal that there has been a correlation between the thickness of boundary layer, the length of wind tunnel, and Reynolds figures, that is, δ/x = 2.1525/Re0.3254; and the correlation between equivalent length and fully developed area was obtained by Le/Dh=3.10 Re1/6. This suggests that the Blansius formula can be applied to determining an equivalent of fully developed area in squared-surface wind tunnels, but the constant changed from 4.4 to. 3.10.